2011
DOI: 10.1590/s0102-76382011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Right coronary artery anatomy: anatomical and morphometric analysis

Abstract: Background: It is necessary knowing the large variability of right coronary (RCA) artery specialty for its implications in surgical procedures and clinic events. This variability is usually related to the length, branches quantity, origin and irrigated territories.Objective: To evaluate by direct examination the morphologic expression of RCA in Colombian people.Methods: RCA were measured in 221 fresh hearts by RCA ostium canalization with polyester synthetic resin that was injected in their branches.Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
38
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 32 publications
15
38
1
6
Order By: Relevance
“…10,11,13,14 In the present study, Co-dominance was found in 1.7%. Comparison of the results of the present study with the results of the various other authors is as follows.…”
Section: Resultssupporting
confidence: 50%
“…10,11,13,14 In the present study, Co-dominance was found in 1.7%. Comparison of the results of the present study with the results of the various other authors is as follows.…”
Section: Resultssupporting
confidence: 50%
“…Coronary CT angiograms studies, Ostium recanalisation with polyester synthetic resin [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…First, the only one patient was involved in this study. Because morphologic expression of coronary artery is different from each other (Ballesteros, et al, 2011), the number of patients directly affects the generality of the result. Second, the resolution of CTA images is not very high, which may more or less affect the accuracy of computational model.…”
Section: Discussionmentioning
confidence: 99%